2009
DOI: 10.1097/pec.0b013e3181ab7885
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial of Lidocaine Gel for Reducing Infant Distress During Urethral Catheterization

Abstract: The use of topical and intraurethral lidocaine resulted in a lower distress when compared with a topical lubricant, at a level approaching significance for global distress. When a subsection of the total distress score that measured infant cry was evaluated, the difference between the intraurethral lidocaine group and the group without intraurethral instillation was statistically significant. Although the results are promising, intraurethral lidocaine did not fully alleviate discomfort associated with urethral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Although bag urine cultures can lead to errors, catheterized urine cultures are not perfect 1 and urethral catheterization is painful, 8 frightening, 9 and risks introducing infection. 10 Fortunately, if other recommendations in the guideline are followed (including the elimination of routine voiding cystourethrograms [VCUGs] and outpatient rather than inpatient antimicrobial therapy; see below), the adverse consequences of falsely positive bag cultures will be markedly attenuated.…”
Section: How Should the Sample Be Obtained?mentioning
confidence: 99%
“…Although bag urine cultures can lead to errors, catheterized urine cultures are not perfect 1 and urethral catheterization is painful, 8 frightening, 9 and risks introducing infection. 10 Fortunately, if other recommendations in the guideline are followed (including the elimination of routine voiding cystourethrograms [VCUGs] and outpatient rather than inpatient antimicrobial therapy; see below), the adverse consequences of falsely positive bag cultures will be markedly attenuated.…”
Section: How Should the Sample Be Obtained?mentioning
confidence: 99%
“…41,42 Studies in younger children, however, are consistent with our findings. Mularoni et al 22 found no significant differences on a global measure of distress in children aged 2 to 24 months undergoing UC. The authors concluded that the administration time of 2 minutes might not have been sufficient for optimal analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely held that UC is painful for both children [17][18][19]22,23 and adults. 39 The suggested practice to reduce UC-related discomfort in children has typically included instillation of an anesthetic gel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations